1999
DOI: 10.1111/j.1365-2559.1999.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined clear and granular cell leiomyoma of soft tissue: evidence of transformation to a histiocytic phenotype

Abstract: Based on these findings, we have interpreted it to be a rare case of leiomyoma with extensive clear cell and granular cell degeneration (combined clear and granular cell leiomyoma). This complete transformation of the immunohistochemical profile into the histiocytic phenotype has not been previously described in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…However, the evidence of ultrastructural and immunohistochemical observations have suggested that a small number of granular cell tumor arises from non‐neural cells. The granular cell tumor comprises a heterogeneous group of neoplasms, so some researchers have adapted the term granular cell leiomyoma or leiomyosarcoma to differentiate it from granular cell schwannoma (Suster et al., 1988; Shimokama and Watanabe, 1992; Dobashi et al., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence of ultrastructural and immunohistochemical observations have suggested that a small number of granular cell tumor arises from non‐neural cells. The granular cell tumor comprises a heterogeneous group of neoplasms, so some researchers have adapted the term granular cell leiomyoma or leiomyosarcoma to differentiate it from granular cell schwannoma (Suster et al., 1988; Shimokama and Watanabe, 1992; Dobashi et al., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Granular cell differentiation is due to an increased number of secondary lysosomes and hallmarked by the presence of abundant eosinophilic granularity of cytoplasm. In the differential diagnosis of GCT, we consider leiomyoma [10], schwannoma [11,12], GIST [6] and xanthoma in GI tract, leiomyoma [13,14], neurofibroma, dermatofibroma, melanocytic nevi [15] and xanthalesma in the skin lesions and fibroma in the oral lesions. In our study, Nestin was positive in GISTs, schwannomas and neurofibromas.…”
Section: Discussionmentioning
confidence: 99%
“…Much has been discussed about the granular nature of GCT cells. Generally, it is believed that it is a response of the tissue to many factors, such as: neoplasia, degenerative or reactive processes like anoxia, metabolic disorders and lysosomic effects (6,7). In the oral cavity, other benign tumors can present granular cells such as granular cell leiomyoma, nonneural granular cell tumor, congenital epulis and also malignancies such as alveolar soft part sarcoma (4).…”
Section: Discussionmentioning
confidence: 99%